The relationship between second-to-fourth digit ratio (2D:4D), muscle strenght and body composition to bone mineral density in young women: 2D:4D, Muscle Strength & BMD in Young Women (Kinesiology, 2019)
Objective: 2D:4D ratio is determined by the balance between androgens to estrogens. Low level estrogen reduces bone mineral density (BMD) and incurs negative changes to bone microarchitecture, increasing the risk of osteoporosis and, as a consequence, fracture risk in women. The purpose of this study was to investigate the relationship between 2D:4D, muscle strength and body composition to BMD in young women.Methods: 127 young women with the age range of 24-36 yr voluntarily participated in this study. Lengths of the second (index) and fourth (ring) fingers, upper and lower body strength and body composition (body mass index (BMI), waist to hip ratio (WHR), body fat percentage) were estimated. Also, blood levels of calcium and 25-hydroxyvitamin D (25OHD) were evaluated and dual-energy X-ray absorptiometry device was used to measure BMD in the lumbar spine (LS) and femoral neck (FN).Results: The results showed that digit ratios, upper body and lower body muscle strength, BMI and fat percentage had a positive relationship with LS and FN BMDs (P˂ 0.05). In addition, there was no significant relationship between WHR and the BMD of LS and FN. Multiple linear regression analysis showed that upper and lower body strength were stronger determinant of BMD LS and FN.Conclusion: Based on the results, the researchers concluded that upper and lower body strength, 2D:4D ratios and BMI are important factors on predict young women’s BMD. Also, it seems that some of these factors may be able to predict the osteoporosis potential in the young women.